Multi-beam backscatter measurements used to infer seabed habits - Kloser, R.; Penrose, John; Butler, A. (Elsevier Ltd, 2010)
Backscatter from multi-beam sonar (MBS) was used to discriminate ecologically relevant seabed characteristics based on 62 reference sites sampled with georeferenced video, sediment grab and rock dredge between 50 and 500 m water depth. A simple biotope characteristic of soft (unconsolidated) and hard (consolidated) was used to compare the acoustic backscatter data with the data on mega-epifauna and substrate type obtained from video and physical sampling. Substrate type of homogeneous reference sites was predicted by matching the backscatter incidence angle profile (0–70°) to that of a seabed scattering model. Referencing the seabed backscatter to a consistent incidence angle (40°) gave a metric with high spatial resolution (2.4–20 m), which minimised errors of range, incident angle and beam compensation. This simple metric provided a consistent approach to analyse and interpret the data and was strongly correlated with substrate type and faunal functional groups. The high resolution backscatter metric was a closer match to the small spatial scale of seabed patch lengths observed by video (50% <50 m).